The Cyclicality of Skill Acquisition: Evidence from Panel Data - Sepulveda-Pizarro, F (2012)
This paper presents new empirical evidence regarding the cyclicality of skill acquisition activities. The paper studies both training and schooling episodes at the individual level using quarterly data from the NLSY79 for a period of 19 years. We find that aggregate schooling is strongly countercyclical, while aggregate training is acyclical. Several training categories, however, behave procyclically. The results also indicate that firm-financed training is procyclical, while training financed through other means is countercyclical; and that the cyclicality of skill acquisition investments depends significantly on the educational level and the employment status of the individual.